Whistleblowing: Don't Encourage It, Prevent It; Comment on "Cultures of Silence And Cultures of Voice: The Role Of Whistleblowing in Healthcare Organisations" - D. Robert MacDougall (Kerman University of Medical Sciences, 2016)
In a recent article, Mannion and Davies argue that there are a multitude of ways in which organizations (such as the National Health Service [NHS]) can deal with wrongdoing or ethical problems, including the formation of policies that encourage and protect would-be whistleblowers. However, it is important to distinguish internal reporting about wrongdoing from whistleblowing proper, because the two are morally quite different and should not be dealt with in the same way. This article argues that we should not understand the authors' conclusions to apply to "whistleblowing" proper, because their recommended approach would be both unfeasible and undesirable for addressing whistleblowing defined in this way.